Aproching optimal depletion path: Natural gas market in Bolivia - Javier Aliaga Lordemann (Universidad Católica Boliviana, Instituto de Investigaciones Socio-Económicas (IISEC), 2009)
This exercise tries to be the first approach in order to understand the overall feedback effects of price path over optimal depletion rate in natural gas market in Bolivia. The simulations attempt to reproduce year-by-year evolution of natural gas depletion. While the initial conditions, parameters the model corresponds to exogenous measures in non linear optimal scheme. Therefore, the numerical values shown in the simulation should not be interpreted as forecasts. Some preliminary key result shows that: opportunity cost of depletion is high especially the first years; companies have low incentives to stop depletion or to be cost-efficient; the effective gas sales to regional markets is not enough yet; contract operation might regards in higher discount rate; exogenous commodity price bid up pressures depletion rate; companies hold expensive ratios of useless reserves related to possible market sales; it is not probable that price path converge with optimal depletion rate neither in short or long run and vice versa.
Keywords: E63; C68; O54; 330; Depletion rate; Discount rate; Natural gas; Price path.